Struggles for recognition : melodrama and visibility in Latin American silent film - Ospina León, Juan Sebastián, 1984- (University of California Press, 2021)
"Struggles for Recognition traces the emergence of melodrama in Latin American silent film and silent film culture. In this deeply archival investigation, Juan Sebastián Ospina León examines how melodrama visualized and shaped the social arena of urban modernity in early twentieth-century Latin America. Analyzing sociocultural contexts through film, this book demonstrates the ways in which melodrama was mobilized for both liberal and illiberal ends, revealing or concealing social inequities from Buenos Aires to Bogotá to Los Angeles. Ospina León critically engages Euro-American and Latin American scholarship seldom put into dialogue, offering an innovative theorization of melodrama relevant to scholars working within and across different national contexts"--